Green Technology in Unmanned Aerial Vehicle (UAV) Electric Propulsion System: A Review - Erwan Eko Prasetiyo; Rustam Asnawi (Institute for Research and Community Service (LPPM), Universitas Malikussaleh, Indonesia, 2025)
The use of fossil energy and coal has a significant impact on global warming through increased greenhouse gas emissions, particularly carbon dioxide (CO2). To address this issue, green technologies offer sustainable solutions, including the development of electric propulsion systems on unmanned aircraft (UAVs). Electric propulsion uses clean energy sources such as batteries and hydrogen fuel cells, significantly reducing emissions and air pollution. This research explores the importance of applying green technologies in the optimization of electric propulsion on UAVs, and the resulting environmental and economic benefits. Electric propulsion technology not only reduces carbon footprint and air pollution, but also improves energy efficiency and extends the operational life of UAVs. In addition, it allows UAVs to operate more quietly, reduces noise pollution, and can be used in various sensitive environments. The implementation of green technologies in UAV electric propulsion systems faces challenges such as limited battery capacity and recharging infrastructure. However, with collaboration between industry, government and research institutions, as well as regulatory support and incentives, the development of these technologies can be accelerated to achieve more environmentally friendly and sustainable UAV operations. Through the application of electric propulsion technology, UAVs are expected to provide innovative and sustainable solutions in areas such as aerial surveying, security surveillance, and freight forwarding, while making a positive impact on the environment and sustainability of the global ecosystem.